2020
DOI: 10.1111/jvim.15703
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 assays for measuring serum total thyroxine concentration in dogs and cats

Abstract: Background No gold standard assay for serum total thyroxine (TT4) concentration in small animals exists. The Microgenics DRI TT4 (MTT4) assay is used by most reference laboratories. Hypothesis/Objectives IDEXX Catalyst Total T4 (CTT4) and Immulite 2000 TT4 (ITT4) results will agree with MTT4 results. Animals Residual small animal sera were randomized before reanalysis (dogs, CTT4 versus MTT4: n = 176, ITT4 versus MTT4: n = 74; cats, CTT4 versus MTT4: n = 319, ITT4 versus MTT4: n = 79). Methods Validation and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Because of the large retrospective nature of this study, it was not possible to provide details of measurement methods in every case. It is recommended that the same assay technique and laboratory are used when monitoring TT4 concentration and a recent study has suggested significant differences between results using different methods, particularly at higher hormone concentrations 19 . In addition, when TT4 concentration was reassessed, this was sometimes tested as part of investigations when the cat was presented for another illness, meaning that TT4 concentration might have been falsely low in some cases, due to nonthyroidal illness.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the large retrospective nature of this study, it was not possible to provide details of measurement methods in every case. It is recommended that the same assay technique and laboratory are used when monitoring TT4 concentration and a recent study has suggested significant differences between results using different methods, particularly at higher hormone concentrations 19 . In addition, when TT4 concentration was reassessed, this was sometimes tested as part of investigations when the cat was presented for another illness, meaning that TT4 concentration might have been falsely low in some cases, due to nonthyroidal illness.…”
Section: Discussionmentioning
confidence: 99%
“…The initial assessment of thyroid status in this case was made based on a total T4 measurement using the IDEXX catalyst in‐house analyser, without the concurrent measurement of canine thyroid stimulating hormone (TSH). While this analyser is found to be accurate for serum total T4 (TT4) concentrations within the reference range 31 . it is conceivable that thyroid hormone autoantibodies, which have reported to be detected in 6.3% of cases diagnosed with hypothyroidism, could have resulted in a falsely normal TT4 result via assay interference 32 .…”
Section: Discussionmentioning
confidence: 99%
“…While this analyser is found to be accurate for serum total T4 (TT4) concentrations within the reference range. 31 it is conceivable that thyroid hormone autoantibodies, which have reported to be detected in 6.3% of cases diagnosed with hypothyroidism, could have resulted in a falsely normal TT4 result via assay interference. 32 A normal TSH would have increased confidence in the diagnosis of euthyroidism at that timepoint, while an elevated TSH may have suggested the patient was in the early stages of the disease, prompting further assessment, for instance measurement of free-T4.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of tT4 in small animal serum samples were stable from 3 months to 2 years when stored at −20 °C [ 9 , 17 , 18 , 19 , 20 ], while human serum tT4 demonstrated a stability for almost 7 years at −80 °C [ 21 ]. Our serum samples were stored from a minimum of 3 months to a maximum of 4 years at −80 °C.…”
Section: Methodsmentioning
confidence: 99%